Identification of antimicrobial resistant bacteria isolated from Hyalomma excavatum and Hyalomma dromedarii infesting camels in Aljouf region, Saudi Arabia - Almutairi, Mashal M.; Alouffi, Abdulaziz; Damra, Eman M.; Alotaibi, Moureq; Alkahtani, Nora S.; Al Salem, Waleed S.; Aljasham, Alanoud T. (Frontiers in Veterinary Science, 2025)
Ticks and tick-borne pathogens are expanding their geographic ranges to novel suitable habitats. Together with the World Health Organization (WHO) and the United Nations (UN), Saudi Arabia’s government has joined efforts to prevent the development of tick-associated pathogens. Here, we investigated the prevalence and diversity of antimicrobial-resistant (AMR) bacteria in ticks parasitizing camels in Al-Jouf province. A total of 60 ticks were sampled and identified as Hyalomma excavatum (n = 41) and Hyalomma dromedarii (n = 19), infesting 11 camels. Altogether 70 bacterial isolates were isolated and subjected to Gram staining, followed by identification using the Vitek 2 compact system. Bacterial isolates consisted of 23 different bacterial species. 68.6% (n = 48) of the total isolates were identified as Gram-positive bacteria, comprising 14 different species, while 31.4% (n = 22) of the total isolates were Gram-negative bacteria, comprising 9 different species. Each collected tick was found positive for at least one bacterial species, however, 9 out of the 70 ticks were found to carry 2 or 3 bacterial species. Antimicrobial susceptibility testings showed that the isolated bacteria exhibited resistance to several clinical antimicrobial agents. The antimicrobial susceptibility profile of Gram-positive bacteria showed that 100% (n = 30) were resistant to benzylpenicillin; 93.3% (n = 28) were resistant to and oxacillin; 56.7% (n = 17) were resistant to clindamycin; 53.3% (n = 16) were resistant to vancomycin; 43.3% (n = 13) were resistant to rifampicin; 40% (n = 12) were resistant to erythromycin and trimethoprim/sulfamethoxazole; 30% (n = 9) were resistant to teicoplanin; 3.3% (n = 1) was resistant to tetracycline. All Gram-positive bacteria were 100% susceptible to linezolid, gentamicin, tobramycin, levofloxacin, moxifloxacin, and tigecycline. Susceptibility testing for Gram-negative bacteria revealed, 75% (n = 12) were resistant to cefoxitin, whereas 68.75% (n = 11) were resistant to ampicillin. 62.5% (n = 10) of the Gram-negative bacteria were resistant to ceftazidime. In addition, 50% (n = 8) were resistant to cephalothin, ceftriaxone, and trimethoprim/sulfamethoxazole; 43.75% (n = 7) were resistant to cefepime; 31.25% (n = 5) were resistant to amoxicillin/clavulanic acid; 6.25% (n = 1) was resistant to nitrofurantoin. However, all Gram-negative bacteria were susceptible to other antimicrobials including piperacillin/ tazobactam, imipenem, meropenem, amikacin, gentamicin, ciprofloxacin and tigecycline. The current study sheds light on the AMR burden in ticks infesting camels in Al-Jouf province.